Toward a better understanding of the role of value in markets and marketing special issue - Vargo, Stephen L., 1945-; Lusch, Robert F. (Review of marketing research,, 2012)
In their 2004 article "Evolving to a new dominant logic for marketing," Vargo and Lusch established the related principles that value is always co-created and, thus, firms cannot deliver value, but only develop compelling value propositions. This perspective is now known as "service-dominant (S-D) logic." Subsequent S-D logic work has suggested that value is not only always co-created; it also requires the integration of resources from multiple sources and thus is contextually contingent, since each instance of value creation involves the availability, integration, and use of a different combination of resources. This repositioning of value, from a static concept of something embedded in the output of a "producer" to be "consumed," to a dynamic concept of a co-created outcome in ever-changing, networked systems, can be seen throughout the manuscripts in this volume.